Assessment of PLS-SEM Path Model for Coefficient of Determination and Predictive Relevance of Consumer Trust on Organic Cosmetics - Suhan; Achar, Anantha Padmanabha (Ushus Journal of Business Management, 2021)
In this paper the researchers investigated the coefficient of determination R-Square and predictive relevance (Q2) through Blindfolding. To fulfil the aim of the study, a structured quantitative research survey has been conducted with 640 sample size. The results emerged from the research survey shows that the R-Square hasmoderate strength for the endogenous latent variable trust and substantial strength or effect for the endogenous latent variables integrity, ability and benevolence. After calculating Q2for the endogenous latent variable ability, benevolence, integrity and trust it was found that the model has predictive relevance for these constructs. The path coefficient threshold values for measuring between indicators namely, cause purview and emotional benefits, cause consequential and trust, cause rubric and trust, cause span and emotional benefits, emotional benefits and trust, functional benefits and trust, ability and trust, benevolence and trust and also for integrity and trust are above the threshold value of 1.96 substantiate the hypothesis and exerts direct relationship between two variables. But the path coefficient threshold values between indicators namely, Cause purview and trust, cause consequential and trust, cause rubric and emotional benefits, cause span and trust, and also self-expressive and trust are below the threshold value of 1.96 does not substantiate the hypothesis and also does not exerts direct relationship between two variables. At the end of the paper, the author highlights the results, along with implications and limitations.